REINTERPRETASI SHALAT JUMAT (KAJIAN DALIL DAN PENDAPAT ULAMA) - Ali Abubakar (Sharia and Law Faculty, 2017)
Orders about the Friday shalat: sermon, shalat, tribune and khatib stick, until opinion of i`adah zuhur after Friday is the parts of Friday ritual made progressively detailed and confessed by some of moslem scholar as Jumhur opinion, at least Syafi`iyah, so that public society assume it as permanent form come from teaching of Rasulullah saw. This article describes construction of Friday at period of Rasul covering history, kaifiyat, categorize the mukallaf, sermon position, and Friday substansi. Research done indicate that there was no complete theorem about procedures of shalat and Friday sermon. This result it become the religious service which multi interpret; very supple, not tighten, and rich with the different idea, so that opened a possibility to be re-expostulated. Theorem of opinion of faction â€œminorityÂ» about orders of Friday can be told stronger rather than Jumhur. Important finding, Friday substansi is syiar of Islam and Friday founded have to with the governmental permit.